2016
DOI: 10.1007/s10995-016-2049-2
|View full text |Cite
|
Sign up to set email alerts
|

Do Social Factors Predict Appropriate Treatment of Child Diarrheal Disease in Peru?

Abstract: Objectives Diarrheal disease is a significant cause of morbidity among children in Peru. Oral rehydration therapy (ORT) is a cost-effective evidence-based approach to treat diarrhea in young children, yet many Peruvian children in poorer households do not receive this life-saving treatment. This study investigates the social determinants of care-seeking behavior and utilization of appropriate home treatment for diarrheal episodes. Methods We used the nationally-representative 2008 Peru Demographic and Health S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Lastly, we mapped the reported use of ORS, yet use is not equivalent to proper preparation of the solution. 47,48 Future studies should examine the factors that have affected ORS coverage, particularly those that have contributed to shortfalls in efforts to increase coverage, to inform future interventions and implementation studies. Future work should also further investigate coverage of zinc treatment, which has shown effectiveness in reducing undernourishment and diarrhoeal mortality in many countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, we mapped the reported use of ORS, yet use is not equivalent to proper preparation of the solution. 47,48 Future studies should examine the factors that have affected ORS coverage, particularly those that have contributed to shortfalls in efforts to increase coverage, to inform future interventions and implementation studies. Future work should also further investigate coverage of zinc treatment, which has shown effectiveness in reducing undernourishment and diarrhoeal mortality in many countries.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we mapped the reported use of ORS, yet use is not equivalent to proper preparation of the solution. 47 , 48 …”
Section: Discussionmentioning
confidence: 99%
“…A study on social determinants of care-seeking in Peru found that rural residence was significantly associated with seeking care for diarrhea. Water source, maternal education and wealth were also significant predictors of seeking care for diarrhea [ 14 ]. Rural communities in South Africa may indicate spiritual and cultural beliefs as being a predictor of receiving care [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings related to the effects of distance and wealth on care utilisation for children under five are consistent with previous studies. Across settings, wealthier households are more likely to seek any, timely and appropriate care [ 31 , 32 , 33 , 34 , 35 , 36 ], and distance to a healthcare facility is inversely related to the frequency and timeliness of care utilisation [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%